Advances in Understanding the Roles of CD244 (SLAMF4) in Immune Regulation and Associated Diseases - Sun, Lin; Gang, Xiaokun; Li, Zhuo; Zhao, Xue; Zhou, Tong; Zhang, Siwen; Wang, Guixia (Frontiers in Immunology, 2021)
Proteins in the signaling lymphocytic activating molecule (SLAM) family play crucial roles in regulating the immune system. CD244 (SLAMF4) is a protein in this family, and is also a member of the CD2 subset of the immunoglobulin (Ig) superfamily. CD244 is a cell surface protein expressed by NK cells, T cells, monocytes, eosinophils, myeloid-derived suppressor cells, and dendritic cells. CD244 binds to the ligand CD48 on adjacent cells and transmits stimulatory or inhibitory signals that regulate immune function. In-depth studies reported that CD244 functions in many immune-related diseases, such as autoimmune diseases, infectious diseases, and cancers, and its action is essential for the onset and progression of these diseases. The discovery of these essential roles of CD244 suggests it has potential as a prognostic indicator or therapeutic target. This review describes the molecular structure and function of CD244 and its roles in various immune cells and immune-related diseases.